PERFORMANCE OF MESHLESS METHOD OF LINES FOR THE SOLUTION OF THE GENERALIZED SEVENTH-ORDER KORTEWEG-DE VRIES EQUATION HAVING APPLICATIONS IN FLUID MECHANICS - Ahmad, Imtiaz; Ahmad, Hijaz; İnç, Mustafa (Vinca Inst Nuclear Sci, 2023)
In this article, we investigate the execution of a meshless method of line (MMOL) to solve general seventh-order Korteweg-de Vries (KdV7) equations numerically. The suggested meshless technique uses radial basis functions (RBF) for spatial derivatives and the Runge-Kutta (RK) method for time derivatives to solve the governing equation. To produce an efficient numerical solution, three different types of RBF are used. The method's output is successfully compared to the exact solution.
Keywords: meshless method of line; radial basis functions; KdV7